Reflections on 20 years of the international tennis federation and olympic solidarity high-performance coach education scholarship programme: Implications for sports coach development - Miguel Crespo; Rafael Martinez-Gallego; Christine Nash (Heliyon)
This paper reflects on the impact of the International Tennis Federation and Olympic Solidarity High-Performance Coach Education Scholarship Programme over the last 20 years. Coach education and development has been identified as key to the advancement of sport performance. This programme has been investigated using an online survey and followed up with semi-structured interviews, with participants and coach developers. Results from the survey suggested that the programme was well received by the tennis coaches and integral to their ongoing development plus the growth of tennis performance in their countries. Follow-up interviews revealed the three key themes of supportive environment, lifechanging experience and level of challenge contributed to the effectiveness of this programme and the subsequent development of tennis performance. This concludes with some recommendations for coach development programmes.